Factors influencing purchase intention of counterfeit products (CDs, DVDs, and downloading music) / Noorhaida Ismail - Ismail, Noorhaida (Faculty of Business and Management, 2007)
KRU Berhad was established with the main objective of meeting the target requirement for 3Q and 4Q 2006. Its main function is to provide the knowledge, business relations, and effective service delivery as a service provider of communications and post productions services. The main objective of this research is to study on "Factors Influencing Purchase Intention of Counterfeit Products (CDs, DVDs, and Downloading Music). KRU Berhad is one of the entertainment companies in Malaysia that faced counterfeit problem. For the purpose of this study, the descriptive research was used, 50 sets of questionnaires were distributed to respondents at Keramat Kuala Lumpur, but only 42 questionnaires were managed to be collected. This research found that respondents are still using counterfeit products because of the lowest price and their availability to get. The purchase intentions have a strong relationship with demographic variables, as can be seen that most of the purchasers are males. In this research, a researcher only focus on the elements of marketing mix that are product, price, place, and promotion as the main indicators of buying counterfeit products. From the findings, the most factor that influence purchasing of counterfeit products is place. Moreover, those factors do not have strong relationship with purchase intention. There are more other factors that influence purchases towards counterfeit products.